Adaptasi Nelayan Pesisir Kabupaten Pacitan Akibat Perubahan Iklim - Luthfi Alif Dinar Choirunnisa; Yunastiti Purwaningsih; Dwi Prasetyani (Jurnal Wilayah dan Lingkungan, 2022)
The phenomenon of climate change is one of the events that affect coastal communities. But in life, there are always changes from several events at a time, namely climate change. With these changes, fishers must adapt to all the changes. The purpose of this study is to analyze the adaptation of coastal fishers in Pacitan Regency to climate change. This study uses the method of library research with the approach used by researchers namely the descriptive analysis approach. The results of the study indicate that adaptation activities due to climate change can be done with three aspects that must synergize for adaptation strategies and minimize the impact of climate change. Adaptation includes environmental adaptation, socio-economic adaptation, and institutional adaptation. Environmental adaptation by protecting coastal areas with mangroves. Socio-economic adaptation by minimizing risk (fisherman's application and insurance), social relations for assistance between fishermen and knowledge management, involvement in adaptation planning in the form of socialization, alternative skills of fishermen for entrepreneurship, and credit facilities to help fishermen's economy. Institutional adaptation by making regulations on climate change adaptation activities that continue to develop.